The music room - Devidayal, Namita 1968- (New Delhi Random House India, 2007)
Based on the story of a young Hindustani classical musician and singer.
Novel.
Keywords: Devidayal, Namita -- 1968- -- Fiction; Kulkarni, Dondutai -- 1923- -- Fiction; Musicians -- India -- Fiction; Singers -- India -- Fiction; Indic fiction (English)